Evaluation of Munich's cycle route planner. Data analysis and customer servey. International scientific conference on mobility and transport tranforming urban mobility, mobil.TUM 2016, 6-7 June 2016, Munich, Germany, - Paul, Florian; Bogenberger, Klaus; Fink, Bernhard (Elsevier, 2016)
A convenient combination of pre- and on trip route information for cyclists are online routing tools. The Munich Transport and Tariff Association in cooperation with the Department of Environment and Health recently developed the MVV Cycle Route Planner. This online route-planning tool can be used either on desktop computers or on smartphones and covers the greater Munich region based on Open Street Map Data. It enables both users and municipalities to add information of cycle routes and other new bicycle infrastructure to the route planner and improve the system continuously. It provides a navigation and map service especially for the requirements of cyclists and can be combined with the use of public transport. This paper concentrates on three different research approaches. In a data analysis more than 130.000 single requests from April until August 2015 were examined with focus on the spatial distribution of origins and destinations in Munich and the suburban region. As a result, the demand and frequency of the user requests give a strong lead where cycle flows are to be expected and further infrastructure, like cycle super highways or improved cycle routes, needs to be considered. A customer survey of users and non-users revealed their mobility patterns and the actual use of the cycle route planner for trips to work or for leisure. The survey focused on usage and assessment of the cycle route planner itself. It further analyzed which means of transport are used for frequent trips and what the restrictions are so far, not to use the bicycle. The article can be downloaded: http://dx.doi.org/10.1016/j.trpro.2016.12.083
Keywords: Individualverkehr; Fahrradverkehr; Fahrrad; Verkehrsplanung; Wegelänge; Routenwahl; Routenplanung; Tourenplanung; Navigation; Fahrradinfrastruktur; Radverkehrsanlage; Radschnellweg; Studie; Befragung